Regul-A: A Technological Application for Sensory Regulation of Children with Autism Spectrum Disorder in the Home Context - Reis, Helena (2022)
Background: Sensory processing disorder is now recognised as a core feature of autism spectrum disorder that influences children’s adaptive behaviours, which, in turn, may interfere with their participation in life situations. This study describes the process of developing a technological platform, in the form of an app, to help families regulate children with ASD, aged 3–6 years old, by applying sensory strategies to improve the child’s participation in daily routines in the home context. (2) Methods: A focus group formed by four specialised occupational therapists who intervene with children with ASD was selected in order to understand and discuss content that should be included in the app. At a later stage, a group of three was involved to ensure quality and veracity in technological platform elaboration. (3) Results: The purpose of the app, named Regul-A, is to help parents regulate children with ASD regarding their participation in home routines. The sensory strategies provided by the focus group in the three major occupations of the child were the first results obtained, followed by the development of the app structure. (4) Conclusions: The next phase of the study will be the use of the platform by families of children with ASD and occupational therapists. It is believed that, in the future, Regul-A will be used as a tool to gather, analyse and manage data on the occupational performance of children with ASD in the home context, particularly for activities of daily living, sleep, rest and play, facilitating the implementation of strategies and the sharing of information between parents and occupational therapists